Infection‐Related Hospitalization and Incident Heart Failure: The Atherosclerosis Risk in Communities Study - Rebecca L. Molinsky; Amil Shah; Melana Yuzefpolskaya; Bing Yu; Jeffrey R. Misialek; Bruno Bohn; David Vock; Richard MacLehose; Barry A. Borlaug; Paolo C. Colombo; Chiadi E. Ndumele; Junichi Ishigami; et al. (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2025)
Background The immune response to infections may become dysregulated and promote myocardial damage contributing to heart failure (HF). We examined the relationship between infection‐related hospitalization (IRH) and HF, HF with preserved ejection fraction, and HF with reduced ejection fraction. Methods and Results We studied 14 468 adults aged 45 to 64 years in the ARIC (Atherosclerosis Risk in Communities) Study who were HF free at visit 1 (1987–1989). IRH was identified using select International Classification of Diseases (ICD) codes in hospital discharge records and was treated as a time‐varying exposure. HF incidence was defined as the first occurrence of either a hospitalization that included an ICD, Ninth Revision (ICD‐9) discharge code of 428 (428.0–428.9) among the primary or secondary diagnoses or a death certificate with an ICD‐9 code of 428 or an ICD, Tenth Revision (ICD‐10) code of I50 among any of the listed diagnoses or underlying causes of death. We used multivariable‐adjusted Cox proportional hazards models to assess the association between IRH and incident HF, HF with reduced ejection fraction, and HF with preserved ejection fraction. Median follow‐up time was 27 years, 55% were women, 26% were Black, mean age at baseline was 54±6 years, 46% had an IRH, and 3565 had incident HF. Hazard ratio (HR) for incident HF events among participants who had an IRH compared with those who did not was 2.35 (95% CI, 2.19–2.52). This relationship was consistent across different types of infections. Additionally, IRH was associated with both HF with reduced ejection fraction and HF with preserved ejection fraction: 1.77 (95% CI, 1.35–2.32) and 2.97 (95% CI, 2.36–3.75), respectively. Conclusions IRH was associated with incident HF, HF with reduced ejection fraction, and HF with preserved ejection fraction. IRH might represent a modifiable risk factor for HF pathophysiology.